Dansk-polsk juridisk-merkantil ordbog - Ptaszynski, Marcin Overgaard (LexicoNordica, 2008)
Anmeldt værk: Grzegorz Okoniewski: Dansk-polsk juridisk-merkantil ordbog. København: Gads Forlag, 1999 [946 sider, DKK 449, ISBN 87-12-03250-6]